2021
DOI: 10.2147/cmar.s320993
|View full text |Cite
|
Sign up to set email alerts
|

Nomogram for the Prediction of Biochemical Incomplete Response in Papillary Thyroid Cancer Patients

Abstract: Purpose: To develop a nomogram for predicting biochemical incomplete response (BIR) in the dynamic risk stratification (DRS) of papillary thyroid carcinoma (PTC) patients without structural recurrence, and to investigate its validity. Patients and Methods: Overall, 1705 (1005 and 700 in the training and validation cohorts, respectively) PTC patients treated with total thyroidectomy without structural recurrence were included. multivariate logistic regression analyses were performed to determine the significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…After adjusting for confounding factors, multivariate analysis demonstrated that only N stage and TNM stage were independent risk factors for RFS. Given that it has been reported that N1b increased the risk of recurrence and death in DTC patients [ [14] , [15] , [16] , [17] ] and N1b was independently identified as a predictor of an unfavorable response to 131 I therapy [ 18 ]. Our study also showed that the RFS rate in the N1b group was significantly lower than that in the N0/N1a group, with a hazard ratio of 2.749.…”
Section: Discussionmentioning
confidence: 99%
“…After adjusting for confounding factors, multivariate analysis demonstrated that only N stage and TNM stage were independent risk factors for RFS. Given that it has been reported that N1b increased the risk of recurrence and death in DTC patients [ [14] , [15] , [16] , [17] ] and N1b was independently identified as a predictor of an unfavorable response to 131 I therapy [ 18 ]. Our study also showed that the RFS rate in the N1b group was significantly lower than that in the N0/N1a group, with a hazard ratio of 2.749.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that N stage was an independent factor for predicting SIR, while the sup-Tg level 6 months post RAT was an independent predictor of IR. Since it has been reported that N1b increased the risk of recurrence and death in DTC patients [19][20][21][22] and N1b was con rmed to be an independent factor predicting unfavorable response to 131 I therapy [23]. Thus, for unexplained elevated Tg with N1b the degree of TSH suppression should be adjusted appropriately and intensive follow-up should be conducted to detect recurrence and metastasis as early as possible.…”
Section: Discussionmentioning
confidence: 99%
“…The other article only predicted incomplete biochemical response in patients but without structural recurrence after total thyroidectomy. 14 Among these models, only three pieces included sonographic features, which predicted PTC diagnosis, but no recurrence.…”
Section: Introductionmentioning
confidence: 99%